Biology and population dynamics of by-catch fish species of the bottom trawl fishery in the western Mediterranean - ORDINES, F.; FARRIOLS, M.T.; LLEONART, J.; GUIJARRO, B.; QUETGLAS, A.; MASSUTÍ, E. (Mediterranean Marine Science, 2014)
The teleosts Chelidonichthys cuculus, Trigloporus lastoviza, Serranus cabrilla and Trachinus draco, are important by-catch species, in terms of landed biomass and commercial value, from the continental shelf bottom trawl fishery off the Balearic Islands (western Mediterranean). The main biological parameters of these species were calculated from monthly biological samplings, and were used along with three years pseudo-cohorts (2008-2010) obtained from monitoring on-board of the bottom trawl fleet, to assess their exploitation level through Virtual Population Analysis (VPA) and Yield per Recruit (Y/R) analysis. Time series of fishery independent indicators based on MEDITS surveys data such as the evolution of the abundance and biomass, the distribution range, and the Conservation Status of Fish b (CSFb), were also analyzed. All four species analyzed showed growth overfishing. The reductions of the fishing effort required to reach the Y/RF0,1 reference point were lower, 66-73% depending on the species, to those reported for the target species M. merluccius (87%), but higher than that reported for M. surmuletus (53%), in the study area in the period 2000-2010. The abundance and biomass, and the distribution range did not show any trend for the period 2001-2011, whereas the CSFb showed signs of recovery that may be due to the displacement of the trawl fishing effort from the shelf to the slope during the last decade. Our results underline the necessary incorporation of monitoring and assessment of by-catch species to the management of fisheries as their populations can show a more pronounced overexploitation than target ones.